Agony and Penance: Sara Lidman in South Africa 1960–1961. Issue 1 (2nd January 2017) - Granqvist, Raoul J
Abstract : The Swedish writer Sara Lidman (1923–2004) wrote Jag och min son ("I and My Son") after a brief stint in apartheid South Africa in 1960–61, from where she was expelled for violation of the Immorality Act. Based on a close, interrelated study of her diary, her letters and the two book manuscripts (first published in 1961; revised and re-published in 1963), I examine the colonial boundary crisis of the Self. The major protagonists in the novels or autobiographies embody, variously, aspects of the writer's angst as it developed in the Johannesburg colonial setting of persecuted ANC members, the elite of the local Swedish community, the friendship of Nadine Gordimer, and the pressure of her anticolonial frustrations.